Investment-Led Growth in China : Global Spillovers - Ahuja, Ashvin (IMF Working Papers; Working Paper ;, 2012)
Over the past decade, China's growth model has become more reliant on investment and its footprint in global imports has widened substantially. Several economies within China's supply chain are increasingly exposed to its investment-led growth and face growing risks from a deceleration in investment in China. This note quantifies potential global spillovers from an investment slowdown in China. It finds that a one percentage point slowdown in investment in China is associated with a reduction of global growth of just under one-tenth of a percentage point. The impact is about five times larger than in 2002. Regional supply chain economies and commodity exporters with relatively less diversified economies are most vulnerable to an investment slowdown in China. The spillover effects also register strongly across a range of macroeconomic, trade, and financial variables among G20 trading partners.